2017
DOI: 10.1186/s40621-017-0102-2
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of homicide perpetration by children

Abstract: BackgroundThe United States has by far the highest rates of homicide perpetration among high-income countries. The perpetration of homicide by children is often newsworthy, but little is known about the incidence or the circumstances of child homicide perpetration.MethodsWe use data from the sixteen states reporting to the National Violent Death Reporting System (NVDRS) for all years 2005–2012. We read every violent death report that was classified a homicide with a child suspect (aged 0–14). To help ensure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
1
8
1
Order By: Relevance
“…For children from birth to 14 years who kill others, NVDRS data revealed boys (90%) more likely to kill than girls. Young males killed infants, a parent, or grandparent, friends (impulsively shot during play), and were more often involved in robbery, and gang violence (Hemenway & Solnick, 2017). Homicide by young girls was rare, and their victims were more often children (0-5 years old), associated with overwhelming childcare responsibilities (younger siblings; Sellers & Heide, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For children from birth to 14 years who kill others, NVDRS data revealed boys (90%) more likely to kill than girls. Young males killed infants, a parent, or grandparent, friends (impulsively shot during play), and were more often involved in robbery, and gang violence (Hemenway & Solnick, 2017). Homicide by young girls was rare, and their victims were more often children (0-5 years old), associated with overwhelming childcare responsibilities (younger siblings; Sellers & Heide, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These findings were consistent with several previous studies’ findings, which indicated that most of the homicides committed by juveniles were motivated by a noncriminal act. (Hemenway & Solnick, 2017; Swart et al, 2015; Vries & Liem, 2011). However, we did not conduct a structured content analyses on the case files and have not been able to determine precisely the dynamics of these fights and arguments in further detail.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, previous studies looking at case characteristics of the homicides committed by juveniles, first, reported that the victims were mostly strangers (Ahonen et al, 2016; Hemenway & Solnick, 2017; Swart et al, 2015; Vries & Liem, 2011). In regard to the weapon of choice in these offenses, Ahonen et al (2016), Cornell, (1993), Hemenway and Solnick (2017), Farrington et al (2012), Heide, Roe-Sepowitz, Solomon, and Chan (2011), and Heide (1993) reported that firearms were the most common weapons used in the cases that they examined. Several other studies reported that sharp objects and knives were also used as weapons in the murder cases committed by juveniles (Chan & Heide, 2008; Rodway et al, 2011b; Vries & Liem, 2011).…”
Section: What Do We Know About Jhos and Their Offenses?mentioning
confidence: 96%
See 2 more Smart Citations